Spatiotemporal Changes in Forest Metrics after a Catastrophic Tornado in Planted Loblolly Pine (Pinus taeda L.) Stands - Simone Lim-Hing; Holly L. Munro; Bronson P. Bullock; Dan M. Johnson; James T. Vogt; Kamal J. K. Gandhi (Forest Science, 2026)
Tornadoes drastically impact managed forest landscapes, altering structure, composition, and economic valuation. Tornadoes occur frequently in the US and are projected to increase in the southeastern region, which is a substantial timber-producing region. Quantifying tornado damage in managed forest landscapes is important for guiding management decisions and modeling recovery efforts to recoup economic losses. We assessed the spatiotemporal effects on forest structure, volume, and carbon in 13–17 year old loblolly pine ( Pinus taeda L.) stands after an EF-3 tornado, with a path length of 35 km long and damage swath of 250 m wide, in Shallotte, North Carolina, US. We established 36 plots along a tornado path and reconstructed pre-storm stand characteristics to compare them to the first and third growing seasons (2021 and 2023) after the storm. To evaluate the spatial distribution of damage, we sampled directly in the tornado’s path, along its edge, and in undisturbed, adjacent forest areas within the same stand. We found that damage was localized, reducing trees per hectare, basal area, volume, and aboveground carbon stock by ~ 50% directly inside the tornado track, while plots located on the edge or in undisturbed forest areas were nominally affected. By the third growing season, all metrics from plots inside the tornado track, except for tree density, increased and stand volume returned to the pre-storm levels. This indicates a rapid recovery in even-aged, spatially uniform pine stands with minimal impacts at the edges and forest interior from the tornadic event. By documenting localized losses and metric-specific recovery of forest structure, this study establishes an empirical baseline for understanding short-term tornado effects in even-aged pine stands, which is important for informing targeted post-disturbance management decisions.

Enhanced fusiform rust hazard maps for loblolly pine: Incorporating genotype and climate to predict disease - Simone Lim-Hing; Cristián R. Montes; Trevor D. Walker; M. Nasir Shalizi; Kamal J.K. Gandhi; Caterina Villari (Forest Ecology and Management, 2024)

Temperature alters the toxicological impacts of plant terpenoids on the polyphagous model herbivore Vanessa cardui - Mari R. Irving; Eric W. Goolsby; Hannah Stanford; Simone Lim-Hing; Maria Urrea; Chase M. Mason (Journal of Chemical Ecology, 2023)
Terpenes are a major class of secondary metabolites present in all plants, and long hypothesized to have diversified in response to specific plant-herbivore interactions. Herbivory is a major biotic interaction that plays out across broad temporal and spatial scales that vary dramatically in temperature regimes, both due to climatic variation across geographic locations as well as the effect of seasonality. In addition, there is an emerging understanding that global climate change will continue to alter the temperature regimes of nearly every habitat on Earth over the coming centuries. Regardless of source, variation in temperature may influence herbivory, in particular via changes in the efficacy and impacts of plant defensive chemistry. This study aims to characterize temperature-driven variation in toxicological effects across several structural classes of terpenes in the model herbivore Vanessa cardui , the painted lady butterfly. We observed a general increase in monoterpene toxicity to larvae, pupa, and adults at higher temperatures, as well as an increase in development time as terpene concentration increased. Results obtained from this study yield insights into possible drivers of seasonal variation in plant terpene production as well as inform effects of rising global temperatures on plant-insect interactions. In the context of other known effects of climate change on plant-herbivore interactions like carbon fertilization and compensatory feeding, temperature-driven changes in plant chemical defense efficacy may further complicate the prediction of climate change impacts on the fundamental ecological process of herbivory.